Recruitment and phosphorylation of SH2-containing inositol phosphatase and Shc to the B-cell Fc gamma immunoreceptor tyrosine-based inhibition motif peptide motif. - Tridandapani, S (1997)
Recently, we and others have demonstrated that negative signaling in B cells selectively induces the tyrosine phosphorylation of a novel inositol polyphosphate phosphatase, p145SHIP. In this study, we present data indicating that p145SHIP binds directly a phosphorylated motif, immunoreceptor tyrosine-based inhibition motif (ITIM), present in the cytoplasmic domain of Fc gammaRIIB1. Using recombinant SH2 domains, we show that binding is mediated via the Src homology region 2 (SH2)-containing inositol phosphatase (SHIP) SH2 domain. SHIP also bound to a phosphopeptide derived from CD22, raising the possibility that SHIP contributes to negative signaling by this receptor as well as Fc gammaRIIB1. The association of SHIP with the ITIM phosphopeptide was activation independent, while coassociation with Shc was activation dependent. Furthermore, experiments with Fc gammaRIIB1-deficient B cells demonstrated a genetic requirement for expression of Fc gammaRIIB1 in the induction of SHIP phosphorylation and its interaction with Shc. Based on these results, we propose a model of negative signaling in which co-cross-linking of surface immunoglobulin and Fc gammaRIIB1 results in sequential tyrosine phosphorylation of the ITIM, recruitment and phosphorylation of p145SHIP, and subsequent binding of Shc.